2022
DOI: 10.1097/prs.0000000000009616
|View full text |Cite
|
Sign up to set email alerts
|

How does oncoplastic surgery compare with standard partial mastectomy? A systematic review of patient reported outcomes.

Abstract: Background: Many breast-conserving surgical options exist for patients with breast cancer. Surgical choices can have lasting effects on a patient’s life, so patient satisfaction is important to assess. Patient-reported outcome measures provide important tools when evaluating surgical modalities. This systematic review aimed to evaluate how patients describe breast-conserving surgical choices in standard partial mastectomy and oncoplastic surgery options. Methods: A Preferred Reporting Items for Systematic Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Rose et al stated patients undergoing oncoplastic breast reconstruction had better health related quality of life outcomes in terms of psychosocial well-being compared to breast conservation surgery alone ( 49 ). A recent meta-analysis of 43 articles including 8,784 patients stated patients undergoing oncoplastic reconstruction had significantly higher scores on all patient-reported outcomes measures compared to standard partial mastectomy ( 50 ). Unfortunately, many patients do not know about the opportunity for reconstruction after a lumpectomy which identifies an area where the breast cancer treatment team has the ability to improve upon patient satisfaction ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rose et al stated patients undergoing oncoplastic breast reconstruction had better health related quality of life outcomes in terms of psychosocial well-being compared to breast conservation surgery alone ( 49 ). A recent meta-analysis of 43 articles including 8,784 patients stated patients undergoing oncoplastic reconstruction had significantly higher scores on all patient-reported outcomes measures compared to standard partial mastectomy ( 50 ). Unfortunately, many patients do not know about the opportunity for reconstruction after a lumpectomy which identifies an area where the breast cancer treatment team has the ability to improve upon patient satisfaction ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review found that women who underwent O-BCS had better sexual well-being and residual skin sensitivity compared to those who underwent mastectomy, despite the type of reconstruction ( 74 ). These findings suggest that preserving the breast tissue and improving breast appearance through oncoplastic techniques can have a positive impact on sexual well-being for breast cancer survivors ( 75 ).…”
Section: Qol Outcomesmentioning
confidence: 99%
“…OPS also improves patient quality of life measured by patient-reported outcome measures (PROMs), such through a BREAST-Q survey ( 4 - 6 ). Measures such as psychosocial well-being have been shown to be higher in patients treated with OPS as compared to BCS.…”
Section: Introductionmentioning
confidence: 99%